'It's difficult, it's life changing what happens to you' patient perspective on life with chronic hypersensitivity pneumonitis: a qualitative study. Issue 1 (31st December 2019) - Aronson, Kerri I; Hayward, Bradley J; Robbins, Laura; Kaner, Robert J; Martinez, Fernando J; Safford, Monika M
Abstract : Rationale: Chronic hypersensitivity pneumonitis (CHP) is a distinct form of interstitial lung disease caused by an inhaled environmental antigen. Some patients with CHP develop progressive pulmonary fibrosis and varying degrees of symptom severity, with heterogeneous impact on functioning and overall well-being. There are no universally accepted diagnostic criteria, few FDA-approved (Food and Drug Administration) therapies and no standardised approach to identifying an antigen. The impact that living with CHP has on patients' quality of life is understudied, preventing the identification of patient-centred research questions and endpoints for future CHP clinical trials. Objectives: We explored patients' experiences, perceptions and expectations of living with CHP. Methods: We conducted semistructured interviews with patients with CHP. Patients were recruited using a purposive heterogeneous sampling strategy. Interviews were audio recorded and transcribed verbatim. Data were analysed using the grounded theory method. Results: Eighteen patients were interviewed. Six major themes emerged from the interviews: (1) suffering due to lack of knowledge and uncertainty, (2) hypervigilance, (3) psychosocial, (4) physical impacts, (5) interpersonal and (6) self-perception and identity. The need to identify and avoid an antigen played a prominent role across the themes and subthemes. Conclusions: We identified several key influences on quality of life in patients with CHP that have not been adequately explored. The prevalence of these influences should be quantified, and they should be included in quality of life assessment and should guide the development of targeted interventions to improve quality of life in this patient population.